SOCIAL AND GEOGRAPHIC ASPECTS IN THE RESEARCH OF AGRIBUSINESS TERRITORIAL ORGANIZATION - Саркісов, А. Ю. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2016)
During Soviet times, the territorial system of agribusiness (agrarian and industrial complex) consisted of large state agricultural and processing companies, agricultural associations. The main integrators and system-forming units at that time were processing plants. In modern terms integrators are not only and not so much processing enterprises as investment companies, large farms with their own processing base and integrated formation that accumulate different stages of agricultural production. Modern agriculture development is characterized by diverse forms of ownership and economic structure shapes farms also as particularly important departure from traditional sectoral management to complex territorial and functional principle of functioning and development. The article proposes a scheme of territorial and functional structure of agriculture, the basis of which we combined as consolidated taxonomy forms of territorial organization and levels of territorial organization. By levels of territorial organization of agribusiness we identify the national level – within the state; regional – the level of the oblast, region; sub-regional – level large parts of the region (seaside of Kherson region); mezo-regional – the level of administrative units, including city councils; micro-regional – within town and village councils and local – within certain villages. In some cases, the presence information database can be continued differentiation territorial levels to a point level – based on individual businesses and business units. The forms of territorial organization include: specialized agricultural areas (zones, districts, sub-districts, areas), agro-industrial system (APS) and agro-industrial clusters. APS is formed based on a type of agro-industrial integration, according to form following systems: agricultural (without specialization); agrarian and industrial, agrarian and financial system. In the formation of any system the main role belongs to the existing links between the main elements (subsystems). By these we mean: organizational and economic relations (organizational, managerial, marketing, agri-service) and technological ties. A new phenomenon in the structure of AIC (primarily within regional AIC) is an agro-industrial clusters. An agricultural cluster is understood by us as a combination of different spatial orientation of the sector companies, organizations and institutions that may be involved in the agro-industrial production and located in geographical proximity to each other. Among them are: agriculture, processing enterprises, research and educational institutions, market infrastructure, etc.